2010
DOI: 10.1136/jcp.2009.072942
|View full text |Cite
|
Sign up to set email alerts
|

Observational and cost analysis of the implementation of breast cancer sentinel node intraoperative molecular diagnosis

Abstract: Intraoperative assessment of SLNs in breast cancer using a molecular assay is a safe, acceptable and accurate technique that allows a reduction in the frequency of delayed axillary clearance surgery. Take-up of this method may be hampered by perverse incentives operating within healthcare funding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…40 Finally, a cost analysis assessment of the OSNA technique was performed at a large UK district general hospital and indicated that there was an implicit savings in reducing the number of secondary surgeries, such as reduced bed occupancy, and this savings may comfortably offset the expense of intraoperative molecular analysis. 45 Another way to allow intraoperative axillary dissection to proceed would be to improve on the intraoperative, cryostat section diagnosis; however frozen sections, have a sensitivity that range from 17% to 92% for micrometastases and from 84% to 94% for macromestastases 19 and do require well trained laboratory technicians.…”
mentioning
confidence: 99%
“…40 Finally, a cost analysis assessment of the OSNA technique was performed at a large UK district general hospital and indicated that there was an implicit savings in reducing the number of secondary surgeries, such as reduced bed occupancy, and this savings may comfortably offset the expense of intraoperative molecular analysis. 45 Another way to allow intraoperative axillary dissection to proceed would be to improve on the intraoperative, cryostat section diagnosis; however frozen sections, have a sensitivity that range from 17% to 92% for micrometastases and from 84% to 94% for macromestastases 19 and do require well trained laboratory technicians.…”
mentioning
confidence: 99%
“…One study measured the costs of intraoperative options that are not relevant to the UK (touch imprint and frozen section) 121 and one study analysed the diagnostic pathway leading to SLN biopsy or ALND. 9,122 The remaining two studies 56,123 were identified as relevant to our review. A second report of the study by Cutress et al 123 was available from the NHS Technology Adoption Centre 124 and was used to complement the information from Cutress et al 123 See Appendix 5 for the quality assessment of all available studies reported in journal articles and Appendix 6 for details of the excluded studies.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Both were single-centre observational studies that compared an intraoperative test with histopathology as the gold standard for assessing SLNB. The study by Cutress et al 123 was set in the UK and assessed the GeneSearch assay whereas the study by Guillen-Paredes et al 56 was conducted in Spain and evaluated the OSNA assay. Both found their respective intraoperative test to be cost-effective compared with histopathology, with both assays being cost-saving while reducing theatre time and length of hospital stay.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their collaboration was sought by NTAC in gathering evidence of cost savings that adoption of BLNA would generate, and findings from a study conducted by them were subsequently published in a peer-reviewed journal. 216 However, Stevens et al 217 point out that 'What is important is that any system for identifying and evaluating new technologies is linked to the system for knowledge dissemination and implementation. It must not stand in splendid isolation'.…”
mentioning
confidence: 99%